Vehicular multihop intelligent transportation framework for effective communication in vehicular ad‐hoc networks. (19th January 2022) - Theerthagiri, Prasannavenkatesan; Gopala Krishnan, Chandrasekaran
Abstract: In the smart city, the presence of intelligent transportation systems (ITS) is much essential. The emerging vehicular ad‐hoc networks (VANET) technology offers a wide range of applications in transportation, mobility, connectivity, and safety applications. In this decade, vehicular traffic is a prime hassle. The actual‐instant traffic data to drivers along with navigation system would facilitate vehicles to select an excellent path. This article proposes hybrid VANET architecture for effective communication between vehicles. The proposed hybrid architecture uses the multihop routing algorithm to permit vehicles to enlarge their driving performance and road safety. The proposed hybrid vehicular multihop routing algorithm with intelligent transportation system (Hybrid VMR‐ITS) allows the transportation system for instantaneous communications between vehicles and road‐side units (RSUs) and vehicles‐traffic servers effectively. The proposed work enhanced the whole spatial usage of a road network by reducing average vehicle travel costs with a reduced traffic overhead of 4%–9% compared with existing works.